Percutaneous laser microdiscectomy in the treatment of multilevel protrusions and herniations of lumbar intervertebral discs - Mykola O. Zorin; Mykola M. Zorin (Ukrainian Neurosurgical Journal)
Objective: To develop a clear treatment strategy for multilevel protrusions and herniations of the lumbar spine using the method of percutaneous laser microdiscectomy (PLMD). Materials and Methods: The study involved 620 patients diagnosed with multilevel lumbar intervertebral disc (IVD) protrusions and herniations, all of whom underwent PLMD. The patients ranged in age from 20 to 50 years, including 360 men and 260 women. All patients underwent preoperative magnetic resonance imaging, and 62% additionally underwent computed tomography. The patients were categorized into four groups: group I (n = 78): PLMD was performed at a single level with herniations characterized by posterior-central or paramedian localization and a sagittal size not exceeding 7 mm; group II (n = 24): PLMD was performed on discs with herniations similar to those in group I, but accompanied by protrusions at other levels (sagittal size 4–6 mm); group III (n = 380): PLMD was performed in a single session on two levels with protrusions (sagittal size 4–6 mm); group IV (n = 138): PLMD was performed in a single session on three levels with protrusions (sagittal size 4–6 mm). All procedures were performed under fluoroscopic guidance using a C-arm system (Phillips, Netherlands). Pain intensity was evaluated using the Visual Analog Scale (VAS) preoperatively and during the two-week postoperative period. Treatment outcomes after one month were assessed using the McNab scale. Long-term quality of life was evaluated using the Oswestry Disability Index. Results: In Group I, the initial radicular pain (measured by VAS) was more severe but significantly decreased after one week postoperatively, while lumbar pain (lumbalgia) remained moderate over the two-week follow-up. In Group II, the reduction in radicular symptoms mirrored that of Group I, with the greatest treatment effect (d = 0.7, p < 0.05); however, lumbalgia only decreased after two weeks (p > 0.05). In Groups III and IV, radicular pain decreased similarly to Group II. However, in Group IV, the intensity of lumbalgia remained high and exceeded the baseline even after two weeks (p > 0.05). At the one-month follow-up, the highest rate of excellent outcomes was observed in Group I and the lowest in Group IV, though differences between the groups were not statistically significant (p > 0.05). These findings suggest that post-PLMD pain severity is largely influenced by lumbalgia rather than radicular pain. Conclusions: Percutaneous laser microdiscectomy is an effective method for treating protrusions and non-sequestered small herniations of the lumbar spine. The method is most appropriate and efficient when performed in a single session for two symptomatic lumbar IVD protrusions. Although it is technically feasible to treat three symptomatic protrusions in a single session, such an approach is considered less advisable.